Strategic management on manufact / Baderisang Mohamed and Nurul Nisa Mat Jamail - Mohamed, Baderisang; Mat Jamail, Nurul Nisa (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
The strategic management lays out the organizational direction by putting in place plans and policies and allocating financial and non-financial resources to execute the plans. The strategic management is crucial to gain a competitive advantage for the organization survivals. Firms use strategy formulation strategies and external audit, which they focus on identifying and evaluating market trends and events beyond their control to achieve defined goals.